KERJASAMA TIM MEMEDIASI DAMPAK KEPEMIMPINAN TRANSFORMASIONAL DAN TRANSAKSIONAL TERHADAP KINERJA KERJA - Hanna Fransiska; Sunjoyo Sunjoyo (Jurnal Manajemen Maranatha, 2019)
The three main objectives of this study are: a) to test and analyze the effects of transformational and transactional leadership to teamwork positively; b) to test and analyze the effect of teamwork direct and positive impact on the performance of the work; c) to examine and analyze the influence of transformational and transactional leadership direct and positive impact on job performance. The study sample consisted of 121 (one hundred and twenty one) leaders who work in 17 (seventeen) private companies operating in the city of Bandung. Two of the five hypotheses are supported, which hypotheses were tested using Structural Equation Modeling (SEM). There are several findings from this study is the first transformational leadership positively affect teamwork, but does not affect the transactional leadership team cooperation positively. The second is teamwork does not affect the performance of work directly and positively. The third is transformational leadership directly affects job performance and positive, but transactional leadership does not affect job performance. The implications of this research was discussed as well as suggestions for future research. Keywords: Transformational Leadership; Transactional Leadership; Teamwork; Job Performance; Leadership Beliefs Inventory (LBI); Practice Environment Survey.